Visual Merchandising Can Moderate the Influence of Hedonic Lifestyle on Purchasing Decisions - Asmah Sinuraya; Hadiansyah Ma’sum; Andriya Risdwiyanto; Yosef Tonce; Kushariyadi (Yayasan Inovasi Kemajuan Intelektual, 2025)
This study aims to analyze the moderating role of visual merchandising on the influence of hedonic lifestyle on purchasing decisions in the modern retail sector. In the contemporary consumerism era, shopping behaviour is no longer based solely on functional needs, but has shifted to a pleasure-seeking activity triggered by a hedonic lifestyle. Using a quantitative approach with a survey method, data were collected from 300 respondents who actively shop in urban shopping centers. The analysis results indicate that a hedonic lifestyle has a positive and significant influence on impulsive purchasing decisions. Furthermore, the main findings of this study revealed that visual merchandising acts as a moderator that strengthens this relationship. The aesthetics of store layout, lighting, and attractive product presentation can stimulate emotional responses in hedonic consumers, which ultimately accelerates the purchasing decision-making process. The implications of this study provide strategic guidance for retail managers to optimize the visual elements of a space to capture a lifestyle-driven market niche.